A Förster Resonance Energy Transfer Switchable Fluorescent Probe With H2S-Activated Second Near-Infrared Emission for Bioimaging - Wang, Rongchen; Gao, Wei; Gao, Jie; Xu, Ge; Zhu, Tianli; Gu, Xianfeng; Zhao, Chunchang (Frontiers in Chemistry, 2019)
Real-time and accurate detection of endogenous hydrogen sulfide is of great biomedical significance. Here, a FRET-based fluorescent probe for ratiometric detection of H2S was designed to comprise an AIE luminophore TPE as and energy acceptor and a monochlorinated BODIPY dye as an energy acceptor and H2S-resposnive site. Such designed probe showed H2S-dependent ratiometric and light-up NIR-II emission, enabling accurate imaging of H2S-rich cancer cells and identification of H2S-rich tumors with high resolution.